2014
DOI: 10.5194/bg-11-7251-2014
|View full text |Cite
|
Sign up to set email alerts
|

Biogeophysical impacts of peatland forestation on regional climate changes in Finland

Abstract: Abstract. Land cover changes can impact the climate by influencing the surface energy and water balance. Naturally treeless or sparsely treed peatlands were extensively drained to stimulate forest growth in Finland over the second half of 20th century. The aim of this study is to investigate the biogeophysical effects of peatland forestation on regional climate in Finland. Two sets of 18-year climate simulations were done with the regional climate model REMO by using land cover data based on pre-drainage (1920… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…Moreover, the forest fraction of the grid cell linearly influences the albedo maximum and minimum values so that they reach values of α sn max = 0.4 and α sn min = 0.3 at a forest fraction of unity (details in Kotlarski, 2007). However, these values of forested α sn max and α sn min are slightly higher than those shown in the literature (e.g., Roesch et al, 2001, and references therein), and therefore in the present work we have reduced both α sn max and α sn min to 0.25 for completely forest-covered grid boxes, following Gao et al (2014). The temperature-dependent α sn takes into account that the snow albedo is lower when snow is wet, i.e., is near the freezing point.…”
Section: The Snow Albedomentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the forest fraction of the grid cell linearly influences the albedo maximum and minimum values so that they reach values of α sn max = 0.4 and α sn min = 0.3 at a forest fraction of unity (details in Kotlarski, 2007). However, these values of forested α sn max and α sn min are slightly higher than those shown in the literature (e.g., Roesch et al, 2001, and references therein), and therefore in the present work we have reduced both α sn max and α sn min to 0.25 for completely forest-covered grid boxes, following Gao et al (2014). The temperature-dependent α sn takes into account that the snow albedo is lower when snow is wet, i.e., is near the freezing point.…”
Section: The Snow Albedomentioning
confidence: 91%
“…In the warmstart method, the model was run for the whole time period with default initial values (for REMO and REMO-FLake separately) and then the model state in July 2014 was used as the initial state for the actual and analyzed simulations (starting in July). More details about the method for the same domain can be found in Gao et al (2014) and Gao et al (2015).…”
Section: Simulationsmentioning
confidence: 99%
“…Thus, abandonment may combine the tree biomass CO 2 sink during the first decades ( Figure 5) with preserving most of the peat. However, keeping the tree stand may warm the climate locally, as forest albedo is lower than that of open mire (Gao et al, 2014;Lohila et al, 2010). Yet, part of this warming may be offset by the higher formation of aerosols and clouds, as trees are important sources of volatile organic compounds (Teuling et al, 2017;Tunved et al, 2006).…”
Section: Global Biogeochemical Cyclesmentioning
confidence: 99%
“…Finding comprehensive data to parameterize and validate historical litter-based activities is not currently possible. To our knowledge, there exist two quantitative studies on traditional non-timber forest uses (Gimmi et al, 2012(Gimmi et al, , 2008. The quantitative studies were localized in Swiss valleys and showed that the model results were sensitive to data such as litter demand for livestock and straw production rate, data which are impossible to find for all of Europe for different times between 1600 and 2010.…”
Section: Litter Demandmentioning
confidence: 99%